Spatio-Temporal Variation Seismicity Pattern in East Java Between 2002 and 2022 Based on the b-value and Seismic Quiescence z-value - Hisyam , Farizky; Susilo , Adi; Anshori, Muhajir; Hasan, Muhammad Fathur Rouf (Trends in Sciences, 2024)
East Java is one of the seismically active regions in part of the Sunda Arc whose seismicity pattern must be studied. Therefore, a spatio-temporal analysis of seismicity between 2002 - 2022 in East Java has been conducted. This analysis aims to investigate the seismotectonic conditions in the East Java region over the last twenty years, especially the seismicity patterns associated with significant earthquakes in East Java. The analysis was carried out by quantifying the spatial and temporal variations of seismicity parameters using b-value and z-value. The used data used are earthquake data from the USGS earthquake catalog during 2002 - 2022 in the East Java region. The analysis was performed using the ZMAP 6.0 program code using the maximum likelihood method. The results of the temporal analysis of b-values show that almost all significant earthquakes in East Java were characterized by a decrease in b-values of up to 0.2. Spatially, the significant earthquake on 10 April 2021 was associated with a low b-value (0.9). Temporal z-value analysis shows that the significant East Java earthquake was preceded by a quiet period (positive z-value) between 4 - 5 years (2003 - 2008 and 2012 - 2016). Spatial analysis of the z-value in the last 7 shows an increase in the z-value before the significant earthquakes occurred on 16 July 2019, 18 March 2020, and 10 April 2021. Therefore, the results of this study indicate that the b-value and z-value potentially can be used as precursors of the significant East Java earthquake. HIGHLIGHTS This is the first time a correlation of b-value and z-value as seismicity parameters has been carried out in East Java, Indonesia, as an attempt to determine the significant earthquake precursors The significant earthquakes in East Java during 2002 - 2022 were marked by a decrease in b-value of up to 0.2 The quiet period in East Java lasted between 4 - 7 years, i.e. 2002 - 2009 and 2012 - 2016, characterized by a positive z-value peaked until +3.5 The z-value at the location of a significant earthquake epicenters show a positive value 2 - 3 years prior to the main quake GRAPHICAL ABSTRACT